Vitamin D Status of Epileptic Children in India: A Prospective Cross-Sectional Study from a Tertiary Care Centre - Azad, Chandrika; Guglani, Vishal; Kaur, Jasbinder; Aulakh, Roosy; Singh, Sukhvinder; Banga, Sumiti (Journal of Child Science, 2020)
Vitamin D deficiency is prevalent all over the world, especially in tropical countries. In epileptics, antiepileptic drugs (AED) and associated comorbidities further impact vitamin D status. The aim of this study is to estimate the prevalence of 25(OH) vitamin D deficiency in epileptic children and evaluate probable risk factors. A cross-sectional study of 200 children between 1 and 18 years of age on AED was undertaken in the pediatric neurology clinic of a tertiary care center of Northern India. In all children, serum 25(OH) vitamin D levels, calcium, phosphorus, and alkaline phosphatase were estimated. The deficiency levels of vitamin D were categorized as: deficiency <20 ng/mL, insufficiency 20 to 30 ng/mL, and sufficiency >30 ng/mL. The potential risk factors for hypovitaminosis D, including type of epilepsy, AED regimen (specific medications, polytherapy vs. monotherapy), cerebral palsy, ambulatory status, intellectual disability, body mass index, gender, and vegetarianism were examined. Among the 200 enrolled children (60% boys), 106/200 (53%) were vitamin D deficient. There was no significant relation of vitamin D levels with gender, type of epilepsy, neurological deficit, and type of AED. An inverse relationship of higher phenytoin doses during monotherapy associated with lower vitamin D levels in monotherapy was found, thereby suggesting adverse effect of high doses of phenytoin on vitamin D levels. VDD is common among epileptic children on AED therapy. Vitamin D deficiency is common prevalent among epileptic children on AED therapy, and its detection and treatment correction should be an integral part of epilepsy management.
Keywords: epilepsy; children; vitamin D deficiency; antiepileptic drugs